Miniaturisation of artificial magnetic conductors: comparison methodology and realisation of compact unit cell. Issue 19 (1st September 2014) - Grau, M.; Serra, R.; Parrón, J.
Abstract : A novel artificial magnetic conductor based on a low‐profile implementation of a capacitively loaded resonant structure is presented, with increased performance in terms of miniaturisation. In addition, a comprehensive analysis of all the parameters involved in downsizing is provided, establishing a fair methodology for comparing the performance of different size reduction strategies.